INCLUSIVE ZAKAT GOVERNANCE LEGAL-THEOLOGICAL PERSPECTIVES AND POLICY INSIGHTS FROM INDONESIA AND MALAYSIA - Fadhilah, Nur; Bariroh, Muflihatul; Febriana, Nina Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study examines inclusive zakat governance in plural societies, focusing on Indonesia and Malaysia, to explore how governance frameworks address the inclusion or exclusion of non-Muslims, the theological and legal arguments that support or resist such inclusivity, and the influence of governance structures on policy outcomes. It specifically addresses three research questions: (1) How do Indonesia and Malaysia’s zakat governance frameworks address the inclusion or exclusion of non-Muslims? (2) What theological and legal arguments support or resist inclusive zakat practices? and (3) How do governance structures influence inclusivity outcomes and policy implementation? Employing a qualitative comparative approach, the study analyzes legal documents, fatwas, policy reports, and scholarly literature through inductive thematic analysis to identify governance patterns, theological debates, and practical challenges. Findings indicate that Indonesia’s hybrid model, combining government oversight with private sector and community participation, shows greater adaptability but faces coordination and trust challenges, while Malaysia’s centralized system ensures procedural consistency yet limits localized innovation and non-Muslim inclusion. Theological and legal interpretations remain divided, with reformist perspectives advocating broader eligibility and traditionalist views emphasizing classical restrictions. Governance mechanisms, including transparency, accountability, and stakeholder engagement, significantly shape inclusivity outcomes. This research contributes to Islamic social finance scholarship by offering a conceptual framework for inclusive and adaptive zakat governance and suggests further exploration of technological integration and interfaith zakat distribution.